Multiple Ischemic Strokes Associated with Childhood Progressive Radiation-Induced Occlusive Cerebral Vasculopathy - Garcez, Daniela; Passos, João; Pedro, Cátia; Nzwalo, Hipólito; Nunes, Sofia; Borges, Alexandra (Journal of Pediatric Neurology, 2020)
There is little knowledge on the pathophysiology of pediatric stroke associated with radiation-induced occlusive cerebral vasculopathy (RIOCV). Herein, we present an extremely rare case of a child with multiple ischemic strokes in association with progressive RIOCV. The possibility of hemodynamic compromise and artery-to-artery embolism as a cause of the ischemic events is discussed.
Keywords: pediatric; stroke; radiation-induced; occlusive cerebral vasculopathy